Pentingnya Pendidikan Kesehatan Kepada Siswa SMA Terhadap Pencegahan TBC di Wilayah Kecamatan Cimalaka Kabupaten Sumedang - Yuliana Rahmat, Delli; Nurfauziah, Esa; Hendrawati, Anjani; Nafisya Rizki, Difa; Agustine Rahardian, Fakhira; Nur Azizah, Heraz; Aziz Ramadhan, K. Fajar; Octaviani Bachtiar, Tiara (LPPM UNINUS, 2024)
Background: Tuberculosis (TB) is a bacterial infection that can affect any part of the human body, but it often affects the lungs, commonly called pulmonary tuberculosis. Positive behaviors have the effect of assisting the state in stabilizing tuberculosis transmission as much as possible. Objective: Community service is carried out to stabilize the possibility of tuberculosis transmission by monitoring, informing, and educating the community in Cimalaka Sub-district, Sumedang Regency. Methods: The speaker presented the material using lectures and assisted by using leaflets that support the material, then given a pre and post-test. Results: This Health Education activity shows results based on pre and post-tests that have been carried out there is no increase in the understanding that tuberculosis can be caused by smoking. Conclusion: Based on the results of the pre and post-tests that have been conducted on respondents, there is an increase in understanding of the signs and symptoms of TB, there is no increase in knowledge that TB cannot be cured within 2 weeks, and respondents already know that bacteria and TB disease can cause TB can be prevented. Keywords: Counseling, Tuberculosis, Students.